2017
DOI: 10.1242/jcs.198853
|View full text |Cite
|
Sign up to set email alerts
|

Caveolae provide a specialized membrane environment for respiratory syncytial virus assembly

Abstract: Respiratory syncytial virus (RSV) is an enveloped virus that assembles into filamentous virus particles on the surface of infected cells. Morphogenesis of RSV is dependent upon cholesterol-rich (lipid raft) membrane microdomains, but the specific role of individual raft molecules in RSV assembly is not well defined. Here, we show that RSV morphogenesis occurs within caveolar membranes and that both caveolin-1 and cavin-1 (also known as PTRF), the two major structural and functional components of caveolae, are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 97 publications
1
25
0
Order By: Relevance
“…Similarly, it was demonstrated that ApoA1 could bind to the Dengue virus and increase its infectivity by promoting its entry into cells, also via SR-BI [98]. This HDL receptor may serve as a receptor for viruses (i.e., the hepatitis C virus) but also appears to be concentrated in cholesterol and sphingolipid-enriched plasma membrane microdomains (lipid rafts) [99], which may serve as a platform for virus entry [100].…”
Section: Hdl and Virusesmentioning
confidence: 99%
“…Similarly, it was demonstrated that ApoA1 could bind to the Dengue virus and increase its infectivity by promoting its entry into cells, also via SR-BI [98]. This HDL receptor may serve as a receptor for viruses (i.e., the hepatitis C virus) but also appears to be concentrated in cholesterol and sphingolipid-enriched plasma membrane microdomains (lipid rafts) [99], which may serve as a platform for virus entry [100].…”
Section: Hdl and Virusesmentioning
confidence: 99%
“…Caveolae are a special subset of lipid rafts (LR) with a distinctive omega shape ranging from 50 to 100 nm in diameter [4346]. The principal component of caveolae is Caveolin 1 (Cav1) [45,47].…”
Section: Introductionmentioning
confidence: 99%
“…Caveolae have been identified as PM domains that recruit calcium regulatory components [44,46], even more it has been reported that in airway smooth muscle (ASM), the PM fraction enriched in caveolae contains several calcium regulatory proteins and that silencing Cav1 reduces SOCE [19,49]. Also, the interplay between Cav1 and SOCE during Xenopus egg meiosis has been reported [14,47].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, RSV G interacts with both RSV M and F protein, which appears to be required for complete virion assembly 26 , 27 . During initial virus entry, RSV glycoproteins have been shown to internalize via clathrin-mediated endocytosis, whereas caveolin is heavily incorporated into the envelope of mature RSV filaments 28 31 . RSV G was also found to be cleaved in the Vero cell line during endosomal recycling, and has been implicated in the maturation and egress of RSV 3 , 5 , 29 , 32 .…”
Section: Introductionmentioning
confidence: 99%